Political transitions in Sudan and Ethiopia: an early comparative analysis. Issue 3 (2nd September 2021) - Verjee, Aly
ABSTRACT: This article presents a comparative analysis of the political transitions occurring in neighbours Ethiopia and Sudan since 2018. To date, these political transitions have largely been analysed independently. While the transition in Sudan is often characterised as a revolution, events in Ethiopia are not usually so described. However, despite the narrative and substantive differences, this article argues that there are important similarities in both countries' contextual circumstances and processes of change. These include the trajectory of concurrent decline of the previous regimes, elements of continuity of the new transitional governments with the previous regimes, societal, especially youth, expectations of change, the rise of a new generation of political leadership, the role of women, the continuing difficulties and challenges of subnational politics, the persistence of economic drivers of political change and discontent, and, most recently, the impact of the COVID-19 pandemic. Moreover, developments in both countries inform and reinforce each other, with consequences for stability and conflict, as the recent prospect of a Sudan-Ethiopia border war starkly demonstrates. Understanding and contextualising the politics of change in one country would benefit from greater comparative analysis of its neighbour.